Densitas dan Fekunditas Tabernaemontana macrocarpa di Komunitas Pinus merkusii, Hutan Lindung Mangunan, Bantul - Atie, Abi Giusti Wohing; Sancayaningsih, Retno Peni (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Tabernaemontana macrocarpa Jack (Cembirit) is a tree species found in Mangunan Conservation Forest and hasn’t been known yet when it appears firstly. Until this time, information about it’s fecundity is still unknown. Pine litter containing allelopathic compound (monoterpen α-pinene and β-pinene) that is toxic to other species. The high density of it’s seedling indicated that pines allelopathy didn’t effect the Cembirit in Pines community. This research purposes to find out the density and fecundity of Cembirit in Pines community. Data collection had been conducted in December 2015 – February 2016 in Mangunan Conservation Forest, Bantul. Data collections were conducted 6 times in 10x10m2 permanent plots. The growth data were analysed using Relative Growth Rate (RGR) analysis. The Cembirit densities in Pines community are 10.420 ind Ha-1 (seedling), 460 ind Ha-1 (sapling), and 40 ind Ha-1 (tree). The Cembirit were categorized into 3 groups based on it’s stem diameter were including 7,7-9,8 cm (group 1), 9,9-11,8 cm (group 2), and 11,9-13,8 cm (group 3). The Cembirit’s RGR are, 0,00079 cm (group 1), 0,00069 cm (group 2), and 0,00055 cm (group 3), with their fecundity are 3,4%, 5,6% and 2,4%. The high density, RGR, and fecundity value of Cembirit, indicated it’s invasiveness and potentialy become a strong competitor for Pines. Keywords: T. macrocarpa, P. merkusii, inavasiveness, Mangunan